Equaliberty in the Dutch Caribbean : ways of being non/sovereign - Pijl, Yvon van der, 1970-; Guadeloupe, Francio, 1971-; Lewis, Linden, 1953-; Allahar, Anton; Allahar, Anton (Critical Caribbean studies., 2022)
"Equaliberty in the Dutch Caribbean is a collection of essays that explores fundamental questions of equality and freedom on the non-sovereign islands of the Dutch Caribbean. Drawing on in-depth ethnographic research, historical and media analysis, the study of popular culture, and autoethnographic accounts, the various contributions challenge conventional assumptions about political non/sovereignty. While the book recognizes the existence of nationalist independence movements, it opens a critical space to look at other forms of political articulation, autonomy, liberty, and a good life. Focusing on all six different islands and through a multitude of voices and stories, the volume engages with the everyday projects, ordinary imaginaries, and dreams of equaliberty alongside the work of independistas and traditional social movements aiming for more or full self-determination. As such, it offers a rich and powerful telling of the various ways of being in and belonging to our contemporary postcolonial world"--